2017
DOI: 10.1055/s-0037-1608675
|View full text |Cite
|
Sign up to set email alerts
|

A Review of the Incidence, Manifestation, Predisposing Factors, and Management of Recurrent Pediatric Inguinal Hernia

Abstract: Recurrent pediatric inguinal hernia is relatively rare. In a large series, the recurrence rates vary from 0.3 to 1.2%. In a university hospital with surgical service for a wide spectrum of sick pediatric patients, the real recurrence rate may be 3 to 6%. Recurrence manifests typically 6 months after first repair. Current evidence indicates that recurrence rates in open and laparoscopic repair are similar. Laparoscopic repairs are, however, still performed by a minority of skilled pediatric surgeons, whereas th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 21 publications
0
7
0
Order By: Relevance
“…The last case, another infant had increased abdominal pressure for a long time after surgery. We found that one of the common features of these patients with recurrence was that they all had increased abdominal pressure and/or violent pull as risk factors shortly after surgery (13,19). These recurrent patients were followed up for another 3 years after reoperation.…”
Section: Discussionmentioning
confidence: 97%
“…The last case, another infant had increased abdominal pressure for a long time after surgery. We found that one of the common features of these patients with recurrence was that they all had increased abdominal pressure and/or violent pull as risk factors shortly after surgery (13,19). These recurrent patients were followed up for another 3 years after reoperation.…”
Section: Discussionmentioning
confidence: 97%
“…The recently reported recurrence rate of laparoscopic inguinal hernia repair in children is 0.3-1.2% 15 .…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, laparoscopy has been widely used in clinical practice with small incisions, slight trauma, few complications, etc ., but studies have shown that there is still a certain recurrence rate after laparoscopic surgery. Therefore, the high-risk factors that cause recurrence after laparoscopic surgery for inguinal hernia have been analyzed, and early prevention and treatment to improve the prognosis of children has been deemed significantly important[ 4 ].…”
Section: Introductionmentioning
confidence: 99%